2011
DOI: 10.1039/c1nj20442d
|View full text |Cite
|
Sign up to set email alerts
|

Donor-substituted triaryl-1,3,5-triazinanes-2,4,6-triones: octupolar NLO-phores with a remarkable transparency–nonlinearity trade-off

Abstract: We report in this letter the measurement of the hyperpolarizabilities of a series of donor-substituted triaryl-1,3,5-triazinanes-2,4,6-triones by hyper Rayleigh scattering (HRS). A remarkable transparency-nonlinearity trade-off is evidenced for these octupolar NLO-phores which might be accessed in a straightforward synthetic way and in a few steps from commercial isocyanates. Scheme 1 Scheme 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…This lack of interest is surprising because, owing to their planar D 3 h or twisted pseudo‐ D 3 symmetry ( A ; Scheme ), these compounds might exhibit significant second‐10 and third‐order11 nonlinear optical (NLO) activities when the central electron‐attracting isocyanurate core is symmetrically decorated with electron‐releasing arms, likewise to related structures based on 1,3,5‐ and 2,4,6‐substituted phenyl derivatives ( B ; Scheme ) 12. In accordance with the first expectation, we have recently shown by hyper Raleigh scattering (HRS) that derivatives such as 1‐X and 2‐X (X=OMe, NMe 2 ) possess remarkable hyperpolarizabilities 14. Given that such octupolar structures might also present good activities for specific third‐order NLO properties, such as two‐photon absorption (TPA),11 we have now completed our previous report on these compounds14 by studying their luminescence and have subsequently used their luminescence to determine the TPA cross sections of selected derivatives.…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…This lack of interest is surprising because, owing to their planar D 3 h or twisted pseudo‐ D 3 symmetry ( A ; Scheme ), these compounds might exhibit significant second‐10 and third‐order11 nonlinear optical (NLO) activities when the central electron‐attracting isocyanurate core is symmetrically decorated with electron‐releasing arms, likewise to related structures based on 1,3,5‐ and 2,4,6‐substituted phenyl derivatives ( B ; Scheme ) 12. In accordance with the first expectation, we have recently shown by hyper Raleigh scattering (HRS) that derivatives such as 1‐X and 2‐X (X=OMe, NMe 2 ) possess remarkable hyperpolarizabilities 14. Given that such octupolar structures might also present good activities for specific third‐order NLO properties, such as two‐photon absorption (TPA),11 we have now completed our previous report on these compounds14 by studying their luminescence and have subsequently used their luminescence to determine the TPA cross sections of selected derivatives.…”
Section: Introductionsupporting
confidence: 76%
“…In accordance with the first expectation, we have recently shown by hyper Raleigh scattering (HRS) that derivatives such as 1‐X and 2‐X (X=OMe, NMe 2 ) possess remarkable hyperpolarizabilities 14. Given that such octupolar structures might also present good activities for specific third‐order NLO properties, such as two‐photon absorption (TPA),11 we have now completed our previous report on these compounds14 by studying their luminescence and have subsequently used their luminescence to determine the TPA cross sections of selected derivatives. Although the synthesis of some of these cyclotrimers has been briefly reported, a more complete account of their synthesis is now disclosed.…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…207 However, Zyss and coworkers 208 showed that octupolar molecules with C 3 symmetry exhibit first hyperpolarizability comparable to those of the donor-acceptor dipoles and a great deal of interest have been devoted to the use of these types of systems for NLO applications. 210 In this respect, the HAT moiety has been identified as a good scaffold to build octupolar systems and the NLO properties of some HAT derivatives (101-103, Fig. 210 In this respect, the HAT moiety has been identified as a good scaffold to build octupolar systems and the NLO properties of some HAT derivatives (101-103, Fig.…”
Section: Nonlinear Optical (Nlo) Properties Of Hat Derivativesmentioning
confidence: 99%